Molecular dynamics investigation of frictional decomposition behavior of HMX-tool interface in diamond cutting of HMX crystals. Issue 3 (22nd February 2021) - Cao, Zhimin; Zong, Wenjun; Zhang, Junjie; He, Chunlei; Huang, Jiaohu; Liu, Wei; Wei, Zhiyong
Abstract : Purpose: This paper aims to reveal the tribochemical reaction mechanism on the nano-cutting interface between HMX crystal and diamond tool. Design/methodology/approach: Molecular dynamics simulation of HMX crystal nano-cutting by the reactive force field is carried out in this paper. The affinity of activated atoms and friction damage at the different interface have been well identified by comparing two cutting systems with diamond tool or indenter. The analyses of reaction kinetics, decomposition products and reaction pathways are performed to reveal the underlying atomistic origins of tribocatalytic reaction on the nano-cutting interface. Findings: The HMX crystals only undergo damage and removal in the indenter cutting, while they appear to accelerate thermal decomposition in the diamond cutting. the C-O affinity is proved to be the intrinsic reason of the tribocatalytic reaction of the HMX-diamond cutting system. The reaction activation energy of the HMX crystals in the diamond cutting system is lower, resulting in a rapid increase in the decomposition degree. The free O atoms can induce the asymmetric ring-opening mode and change the decomposition pathways, which is the underlying atomistic origins of the thermal stability of the HMX-diamond cutting system. Originality/value: This paper describes a method for analyzing the tribochemical behavior of HMX and diamond, which is beneficial to study the thermal stability in the nano-cutting of HMX.